RANCANG BANGUN SISTEM INFORMASI PENGELOLAAN DAN PEMBELIAN INVENTARIS PADA CV.LUCIANA JAYA SEMARANG (Information Technology and Telematics, 2013)
Abstract -Application System Inventory management and purchasing a data warehouse is an Information technology for ease of warehouse administration activities. This study aims to design a media presentation of information in the Inventory Items Luciana CV Jaya Semarang, particularly information regarding inventory data,  supplier  data,  reports  that  the  purchase  will  be given to the managerial head in particular. This application uses themethodology of system development life     cycle has fivestages-planing, analysis, design, implementation and  evaluation. This application is built using PHP programming language and MySQL as database. The advantages of this programming language that can create a website that is dynamic, easy to make,can berun ina different webserver, is freeware(free), and includesserver sideprogramming. Keywords :system development life cycle, website, web server, server side programing